Temperature evolution of hydration shells in solid DNA didecyldimethylammonium chloride complex studied by 1H NMR spectroscopy. (May 2015) - Nizioł, Jacek; Nowak, Piotr; Kobierski, Jan; Harańczyk, Hubert
Abstract : Graphical abstract: Highlights: First hydration shell in DNA is completely filled at 80% RH (literature). Experimental results indicate that mobile water fraction exists already at 10.1% RH. Second hydration shell starts to built up before primary shell is fully filled. Alternatively, water can accumulate in lipid structures surrounding DNA helix. Abstract: In the case of DNA and its derivatives hydration effect are of paramount importance for many characteristics. Despite years of extensive research this phenomenon is not completely understood yet. A model DNA–lipid complex with didecyldimethylammonium chloride was subjected to gaseous phase hydration procedure. Using 1 H NMR spectroscopy a qualitative change in hydration pattern was identified when the material was conditioned in atmosphere of 10.1% of relative humidity. At the threshold hydration level on the top of the first hydration shell appear water molecules that may be attributed to the second hydration shell. This value is lower, that cited in the bibliography as the saturation point of the first hydration level.